Assessment of Patient Safety Culture at a Private Hospital in Surabaya: A Cross-Sectional Study Using HSOPSC 2.0 - Margarita, Livia; Chalidyanto, Djazuly; Marlia Tanaya, Evelyn (Universitas STRADA Indonesia, 2025)
Patient safety remains a global health priority and a key indicator of hospital service quality. This study aims to assess the patient safety culture at a private hospital in Surabaya, Indonesia. A descriptive cross-sectional study was conducted using the HSOPSC 2.0 questionnaire from AHRQ. A total of 222 hospital staff responded. The overall positive patient safety culture score was 62%, categorized as average. The highest-scoring dimensions were teamwork (80%), organizational learning-continuous improvement (79%), and communication about errors (77%). Conversely, the lowest-scoring dimensions were staffing and work tempo (24%), patient safety incident reporting (46%), and response to errors (48%). Regular patient safety culture surveys along with improvement intervention are essential for continuous quality improvement in hospital settings.